FREKUENSI MENYUSUI, TEKNIK MENYUSUI, DAN PERAWATAN PAYUDARA DENGAN BENDUNGAN ASI - Endriyani Syafitri; Muthia Sari Mardha; Winda Agustina (Universitas Prima Indonesia, 2022)
Swollen breasts will show breast edema, the patient feels pain, the nipples are tight, the skin is shiny even though it is not red, the milk will not come out when examined or sucked, and the body has a fever after 24 hours. The purpose of this study was to analyze the relationship between breastfeeding frequency, breastfeeding technique, and breast care with breast milk dams in mothers at the independent midwife practice Romauli Silalahi. The research method used is an analytical survey with a cross sectional approach. The research location was at the Romauli Independent Midwife Practice Medan Marelan, the time of the study was March-August 2021. The population in this study were postpartum mothers at the Romauli Silalahi Independent Midwife Practice as many as 30 people. the sample was taken by the total sampling technique. Data analysis used univariate and bivariate analysis using chi-square test. The results showed that based on the chi-square test on the relationship between breast milk dams and breastfeeding mothers, p-value = 0.002 was obtained, the frequency of breastfeeding with the incidence of breast milk dams was obtained p-value = 0.037, and breast care with the incidence of breast milk dams was obtained p-value = 0.023. The conclusion showed a significant relationship between breastfeeding technique, frequency of breastfeeding and breast care with breast milk dams in breastfeeding mothers at the Romauli Silalahi Independent Midwife Practice. It is hoped that the results of this research can be applied by respondents by paying more attention to the milk intake that babies get and doing breast care more often.